2020
DOI: 10.18330/jwallacea.2020.vol9iss1pp43-49
|View full text |Cite
|
Sign up to set email alerts
|

Bark Characteristics of Acacia auriculiformis A. Cunn. ex Benth. and Acacia mangium Willd. From Industrial Plantation Forest

Abstract: Increasing the value of bark can be known through the characteristics of the bark such as physical properties, the grade of fiber quality and the chemical composition of the bark. The purpose of this study is to find out the characteristics of the bark of the acacia plant species (i.e. Acacia auriculiformis and Acacia mangium) of Industrial Plantation Forest. The characteristics of the bark observed includes physical properties, quality grade of fiber and chemical composition. The results of this study showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…The results of the analysis using GC-MS are depicted in the GC spectra of Figure 5. This study has been previously reported [20]. Identification of compounds from the bark of A.auriculiformis showed high yields, namely phenyl phenol 33.6%.…”
Section: Analysis Of Extractives By Gc-mssupporting
confidence: 72%
See 2 more Smart Citations
“…The results of the analysis using GC-MS are depicted in the GC spectra of Figure 5. This study has been previously reported [20]. Identification of compounds from the bark of A.auriculiformis showed high yields, namely phenyl phenol 33.6%.…”
Section: Analysis Of Extractives By Gc-mssupporting
confidence: 72%
“…The effectiveness of vegetable tanning agents can be done through the extraction of tannins. Extraction of tannins from various plants as tanning agents has been carried out in previous studies [20]. Tannin compounds are polar in the form of glycosides [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation